The impact of varying levels of residual disease following cytoreductive surgery on survival outcomes in patients with ovarian cancer: a meta-analysis - Dana M. Chase; Anadi Mahajan; David Alexander Scott; Neil Hawkins; Linda Kalilani (BMC, 2024)
Abstract Background Residual disease following cytoreductive surgery in patients with ovarian cancer has been associated with poorer survival outcomes compared with no residual disease. We performed a meta-analysis to assess the impact of varying levels of residual disease status on survival outcomes in patients with ovarian cancer who have undergone primary cytoreductive surgery or interval cytoreductive surgery in the setting of new therapies for this disease. Methods Medline, Embase, and Cochrane databases (January 2011 - July 2020) and grey literature, bibliographic and key conference proceedings, were searched for eligible studies. Fixed and random-effects meta-analyses compared progression and survival by residual disease level across studies. Heterogeneity between comparisons was explored via type of surgery, disease stage, and type of adjuvant chemotherapy. Results Of 2832 database and 16 supplementary search articles screened, 50 studies were selected; most were observational studies. The meta-analysis showed that median progression-free survival and overall survival decreased progressively with increasing residual disease (residual disease categories of 0 cm, > 0-1 cm and > 1 cm). Compared with no residual disease, hazard ratios (HR) for disease progression increased with increasing residual disease category (1.75 [95% confidence interval: 1.42, 2.16] for residual disease > 0-1 cm and 2.14 [1.34, 3.39] for residual disease > 1 cm), and also for reduced survival (HR versus no residual disease, 1.75 [ 1.62, 1.90] for residual disease > 0-1 cm and 2.32 [1.97, 2.72] for residual disease > 1 cm). All comparisons were significant (p < 0.05). Subgroup analyses showed an association between residual disease and disease progression/reduced survival irrespective of type of surgery, disease stage, or type of adjuvant chemotherapy. Conclusions This meta-analysis provided an update on the impact of residual disease following primary or interval cytoreductive surgery, and demonstrated that residual disease was still highly predictive of progression-free survival and overall survival in adults with ovarian cancer despite changes in ovarian cancer therapy over the last decade. Higher numerical categories of residual disease were associated with reduced survival than lower categories.